2021
DOI: 10.3389/fimmu.2020.611133
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets Convert CD14+CD16- Into CD14+CD16+ Monocytes With Enhanced FcγR-Mediated Phagocytosis and Skewed M2 Polarization

Abstract: Monocytes are important cellular effectors of innate immune defense. Human monocytes are heterogeneous and can be classified into three distinct subsets based on CD14 and CD16 expression. The expansion of intermediate CD14+CD16+ monocytes has been reported in chronic inflammatory diseases including rheumatoid arthritis (RA). However, the mechanism underlying induction of CD16 and its role in monocytes remains poorly understood. Here, we demonstrate that activated platelets are important for induction of CD16 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 71 publications
(124 reference statements)
0
20
1
Order By: Relevance
“…These findings suggest that an inflammatory environment contributes to the binding of PLT to monocytes with a regulatory effect. Whereas, like other authors, we have not found any statistical association between PLT activation markers and disease activity [ 50 ], Lee et al found a correlation between sCD62P levels and disease activity, CRP and ESR [ 51 ]. This discrepancy between studies may be due to differences in cohort characteristics.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These findings suggest that an inflammatory environment contributes to the binding of PLT to monocytes with a regulatory effect. Whereas, like other authors, we have not found any statistical association between PLT activation markers and disease activity [ 50 ], Lee et al found a correlation between sCD62P levels and disease activity, CRP and ESR [ 51 ]. This discrepancy between studies may be due to differences in cohort characteristics.…”
Section: Discussioncontrasting
confidence: 58%
“…It is possible that IL-6 modifies the activation status of monocytes. Another possibility is that IL-6 induces CD16 expression on monocytes and PLTs would therefore preferentially bind to CD16+ monocytes [ 34 , 37 , 51 ]. This is unlikely in our settings because we did not find differences in CD16 expression on monocytes cultured for 28 h with or without rhIL-6 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…35 Finally, a recent study by Lee et al demonstrated that activated platelets skewed monocyte differentiation to the M2 subset and can even convert some monocytes from M1 to M2. 36 Put together, it is clear that the monocytes found in PRP have the potential to significantly modulate the inflammatory environment at the site of local injection.…”
Section: Lymphocytesmentioning
confidence: 99%
“…Beyond their hemostatic activity, activated platelets trigger NET formation and modulate cellular functions of adjacent immune cells [48]. This study, among others, has provided evidence that activated platelets, as well as pEVs, induce a shift towards inflammatory CD16 + monocyte subsets [49][50][51], which has been implicated in disease severity in sepsis as well as in COVID-19 [52]. Furthermore, numerous studies have consistently demonstrated platelet hyperactivation in COVID-19 patients, especially in those with severe disease [2].…”
Section: Discussionmentioning
confidence: 56%